Surface charge impact in low-magnesium model of seizure in rat hippocampus - Isaev, Dmytro (American Physiological Society, 2012)
Putative mechanisms of induction and maintenance of seizure-like activity (SLA) in the low Mg(2+) model of seizures are: facilitation of NMDA receptors and decreased surface charge screening near voltage-gated channels. We have estimated the role of such screening in the early stages of SLA development at both physiological and room temperatures. External Ca(2+) and Mg(2+) promote a depolarization shift of the sodium channel voltage sensitivity; when examined in hippocampal pyramidal neurons, the effect of Ca(2+) was 1.4 times stronger than of Mg(2+). Removing Mg(2+) from the extracellular solution containing 2 mM Ca(2+) induced recurrent SLA in hippocampal CA1 pyramidal layer in 67% of slices. Reduction of [Ca(2+)](o) to 1 mM resulted in 100% appearance of recurrent SLA or continuous SLA. Both delay before seizure activity and the inter-SLA time were significantly reduced. Characteristics of seizures evoked in low Mg(2+)/1 mM Ca(2+)/3.5 K(+) were similar to those obtained in low Mg(2+)/2 Ca(2+)/5mM K(+), suggesting that reduction of [Ca(2+)](o) to 1 mM is identical to the increase in [K(+)](o) to 5 mM in terms of changes in cellular excitability and seizure threshold. An increase of [Ca(2+)](o) to 3 mM completely abolished SLA generation even in the presence of 5 mM [K(+)](o). A large variation in the ability of [Ca(2+)](o) to stop epileptic discharges in initial stage of SLA was found. Our results indicate that surface charge of the neuronal membrane plays a crucial role in the initiation of low Mg(2+)-induced seizures. Furthermore, our study suggests that Ca(2+) and Mg(2+), through screening of surface charge, have important anti-seizure and antiepileptic properties.